KONTRIBUSI MUFASIR NUSANTARA DALAM MENJAGA PRINSIP WASATHIYAH: Studi Analisis Tafsir Al-Nur, Al-Azhar dan Al-Misbah - Rozaq, Abd (Muta’allim: Jurnal Pendidikan Agama Islam, 2025)
Nusantara mufasir developed at the same time as Islam entered Indonesia, such as Hasby ash-Shiddiqie with his tafsir al-Nur, Hamka with his tafsir al-Azhar and Quraish Shihab with his tafsir al-Mishbah. These three figures have strong popularity and influence. Researchers in this context want to explore in more detail the interpretation of wasathiyah principles and their contribution, where recently the issue of moderation has developed due to the emergence of extreme understanding. By using a qualitative descriptive analysis method which is included in the library research category, researchers will explore references in the form of three tafsir books from each commentator and written reference sources related to the research theme. From the results of the systematic research, the presentation of the three tafsir uses the standard coherent systematics of the Ottoman Mushaf, with the same language style using popular writing. As for the form of writing, the tafsir of an-Nur and al-Azhar use a scientific form of writing, while al-Mishbah uses non-scientific writing. While the nature of the exegesis was all carried out individually with the exegetical knowledge obtained by Hasbi and Hamka autodidactically and Quraish Shihab which was achieved through formal education, the origins of all literature came from non-academic writing. Abstrak Mufasir nusantara berkembang bersamaan dengan agama Islam masuk ke Indonesia, seperti Hasby ash-Shiddiqie dengan tafsir al-Nur nya, Hamka dengan tafsir al-Azhar nya dan Quraish Shihab dengan tafsir al-Mishbahnya. Tiga tokoh ini mempunyai popularitas dan pengaruh yang kuat. Peneliti dalam kontek ini ingin menelusuri lebih terperinci penafsiannya mengenai prinsip-prinsip wasathiyah serta kontribusinya, yang mana pada akhir- akhir ini isu moderasi berkembang sebab munculnya pemahaman yang ekstrim. Dengan menggunakan metode analisis deskriptif kualitatif yang termasuk dalam kategori library research peneliti akan menggali dari referensi yang berupa tiga kitab tafsir dari masing- masing mufasir dan sumber- sumber rujukan tertulis yang berkaitan dengan tema penelitian. Dari hasil penelitian Sistematika penyajian ketiga tafsir menggunakan sistematika runtut standart mushaf utsmani, dengan gaya bahasa yang sama-sama menggunakan penulisan popular. Adapun bentuk penulisannya tafsir an-Nur dan al-Azhar menggunakan bentuk penulisan ilmiah sedangkan al-Mishbah menggunakan penulisan non ilmiah. Sementara sifat mufasirnya semuanya dilakukan secara individual dengan keilmuan mufasirnya yang didapat Hasbi dan Hamka secara otodidak dan Quraish Shihab yang ditempuh dengan pendidikan formal,asal-usul literatur kesemuanya berasal dari penulisan non akademik.